Efficacy of artesunate combined with Atractylodes lancea or Prabchompoothaweep remedy extracts as adjunctive therapy for the treatment of cerebral malaria - Walaiporn Plirat; Prapaporn Chaniad; Arisara Phuwajaroanpong; Atthaphon Konyanee; Parnpen Viriyavejakul; Abdi Wira Septama; Chuchard Punsawad (BMC, 2023)
Abstract Background Cerebral malaria is one of the most serious complications of Plasmodium infection and causes behavioral changes. However, current antimalarial drugs have shown poor outcomes. Therefore, new antimalarials with neuroprotective effects are urgently needed. This study aimed to evaluate the effects of selected extracts as monotherapy or adjunctive therapy with artesunate on antimalarial, anti-inflammatory, antioxidant, and neuroprotective properties in experimental cerebral malaria (ECM). Methods ECM was induced in male C57BL/6 mice by infection with Plasmodium berghei ANKA (PbA). Ethanolic extracts of Atractylodes lancea (a dose of 400 mg/kg) and Prabchompoothaweep remedy (a dose of 600 mg/kg) were evaluated as monotherapy and adjunctive therapy combined with artesunate at the onset of signs of cerebral malaria and continued for 7 consecutive days. Parasitemia, clinical scores, and body weight were recorded throughout the study. At day 13 post-infection, mouse brains were dissected and processed for the study of the inflammatory response, oxidative stress, blood-brain barrier (BBB) integrity, histopathological changes, and neurocognitive impairments. Results Ethanolic extracts of A. lancea and Prabchompoothaweep remedy alone improved cerebral malaria outcome in ECM, whereas artesunate combined with extracts of A. lancea or Prabchompoothaweep remedy significantly improved the outcome of artesunate and crude extracts alone. Using real-time PCR, PbA-infected mice that had received the combination treatment showed significantly reduced gene expression of inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-10), chemokines (CXCL4 and CXCL10), and adhesion molecules (ICAM-1, VCAM1, and CD36). The PbA-infected mice that received the combination treatment showed a significantly decreased malondialdehyde level compared to the untreated group. Similarly, the Evans blue dye assay revealed significantly less dye extravasation in the brains of infected mice administered the combination treatment, indicating improved BBB integrity. Combination treatment improved survival and reduced pathology in the PbA-infected group. Additionally, combination treatment resulted in a significantly reduced level of cognitive impairment, which was analyzed using a novel object recognition test. Conclusions This study demonstrated that artesunate combined with A. lancea or Prabchompoothaweep remedy extracts as adjunctive therapy reduced mortality, neuroinflammation, oxidative stress, BBB integrity protection, and neurocognitive impairment in the ECM.